Case Report: Metastatic lung cancer in Meckel's Cave: a radiotherapy successful case and literature review - Chen, Chao; Lu, Zhiqin; Lin, Gang; Hu, Yujie; Guo, Yong (Frontiers in Oncology, 2025)
BackgroundMeckel’s cave (MC) is a highly uncommon site for metastatic disease, particularly from primary lung cancer.Case presentationWe report a clinical case of a 70-year-old man presenting with left trigeminal pain, left ptosis, and restricted abduction of the left eyeball. The patient had a 2-year history of stage IV lung squamous cell carcinoma. Contrast-enhanced brain MRI and FDG-PET/CT showed an ill-defined mass with a heterogeneously enhancing lesion involving the left MC and middle cranial fossa. Stereotactic radiosurgery (SRS, 30 Gy/5 fx) achieved significant improvement in symptoms and regression of radiologic tumors within 1 month. Our review of relevant literature identified only two reported cases of lung adenocarcinoma metastasizing to MC. In addition, we examined the limited literature on other malignant tumors metastatic to MC managed with radiotherapy.ConclusionThis is the first reported case of MC metastasis from lung squamous cell carcinoma successfully treated with SRS. Effective management of MC metastasis requires histology-specific radiotherapy strategies, with squamous cell carcinoma benefiting from hypofractionated SRS.